RESILIENSI ISTRI PERTAMA YANG MENJALANI KEHIDUPAN POLIGAMI - El Zahra Rafida Salsabila; Andhita Dyorita Khoiriyasdien (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2026)
This study aims to explore the resilience dynamics of first wives in polygamous marriages. A qualitative case study approach was used to understand the subjective experiences, adaptation processes, and sources of psychological resilience of the subject. The participant was a 60-year-old woman who has been the first wife in a polygamous marriage for approximately 25 years. Data were collected through in-depth interviews and observation, with thematic analysis based on the dimensions of the Connor-Davidson Resilience Scale (CD-RISC). The results reveal that the subject’s resilience was built through the interaction of personal competence centered on motherhood, coping strategies that evolved from external support to spiritual approaches, positive acceptance of change, and self-control rooted in emotional awareness and religious faith. Spirituality was found to be the core foundation of resilience, where suffering due to polygamy was transformed into meaning and strength through a relationship with God. Confirmation from a significant other reinforced the finding that the subject had reached a stage of acceptance, independence, and post-traumatic growth. This study concludes that resilience in the context of polygamy is transformative, involving a long process of adaptation, meaning-making, and life reorientation toward autonomy and psychological well-being.